Evaluasi Plant Growth-Promoting Bacteria (PGPB) Indigenus Perakaran Kelapa Sawit Pada Pembibitan Kelapa Sawit - Fandi Hidayat; Yudha Yudhistira; Rizki Desika Putri Pane; Fadilla Sapalina; Eka Listia; Winarna Winarna (Pusat Penelitian Kelapa Sawit, 2023)
Achieving sustainability in oil palm cultivation depends on maintaining soil health. Various methods have been employed to improve soil productivity, including the use of plant growth-promoting bacteria (PGPB). Identifying and utilizing superior PGPB strains as biofertilizers can be a solution to enhance soil productivity. Four PGPB candidate strains – NT2, NT5, PD1, and PK1 – were isolated from the oil palm rhizosphere, identified as Azotobacter chroococcum, Azospirillum brasilense, Bacillus alkalicellulosilyticus, and Pseudomonas brassicacearum, respectively, and confirmed as multifunctional PGPB through qualitative and quantitative trait screening. Application of the PGPB consortium as biofertilizer in oil palm nurseries has shown effectively increase nutrient uptake, growth performance, biomass production, and reduce inorganic fertilizer usage by up to 50%. Furthermore, this biofertilizer was found to be 7-30% more efficient compared to 100% inorganic fertilizers.